Evaluation of Ground Reaction Forces and Limb Symmetry Indices Using Ground Reaction Forces Collected with One or Two Plates in Dogs Exhibiting a Stifle Lameness - Pettit, Elizabeth M.; Sandberg, Gabriella S.; Volstad, Nicola J.; Norton, Megan M.; Budsberg, Steven C. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of the study was to evaluate the efficiency and consistency in the collection of ground reaction forces using one or two force plates from dogs with stifle lameness.Animals Twenty-two client-owned dogs with unilateral stifle lameness were used.Methods In a prospective study design, data were collected at a single time point using both one- and two-plate collection methods. Ground reaction forces collected included peak vertical force, vertical impulse and associated symmetry indices. Additionally, time required to obtain valid trials and the total number of trials were also recorded for both one-plate and two-plate collections. Linear mixed models were used to analyse differences in peak vertical force, vertical impulse and symmetry indices between the collection methods. A paired-T test was used to compare trial number and time of trial collection. The significance threshold was p < 0.05.Results It took significantly longer to collect valid trials using one-plate both in time (16.1 ± 8.0 minutes vs, 8.0 ± 4.3 minutes with two plates) and number of trials (33.8 ± 14.8 trials vs. 16.4 ± 8.8 trials with two plates) (p < 0.0001). There was no difference in peak vertical force or vertical impulse data between collection methods. Neither the peak vertical force symmetry indices nor the vertical impulse symmetry indices were significantly different between one- and two-plate collection techniques.Conclusion The total time and number of trials needed to collect valid trials in dogs with stifle lameness were minimized through the use of two force plates. However, there was no significant difference in the ground reaction force or symmetry index values collected between the two systems.
Keywords: force plate; ground reaction forces; dog; symmetry indices; lameness